Chosen health behaviours of women in the context of motherhood experience - Mianowana, Violetta; Dobrowolska, Beata; Bednarek, Anna; Cuber, Tomasz; Dzioboń, Małgorzata (Nursing in the 21st Century, 2011)
The health status of an individual, and in consequence, the average life expectancy depends on a number of factors but the most important and indisputable seems to be the style of living - 53%. The perspective of motherhood is one of the most significant and unique event in the life of each family life. It is an extraordinary period of life for women because each of them wants to have a healthy offspring. But they are not always aware of what is potentially the best for newborn. And this is why educational and health promoting activities are important. Modern obstetrics in its basic activities is focused on preventive measures to protect the health of the mother and her offspring, and the whole family. The aim of the study was to answer the question whether the experience of motherhood is a factor that influences the improvement of healthy behaviour and if the growing experience of motherhood influences more caring for oneself and family health . Motherhood is a valuable experience that seems to let verify own view on life style and often becomes motivation for the effective healthy actions addressed to self and own offspring. Apparently, the experience of motherhood does not have to indicate progressive healthy behaviour, as the study confirmed.